Analisis Efisiensi Energi Pada Proses Produksi Gula Di PT Madubaru - Moh. Rifki Januar; Yohanes Anton Nugroho (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2023)
PT Madubaru is a company that produces granulated sugar, spritus and alcohol. Granulated sugar is the main product produced by PT Madubaru. This study aims to analyze the energy efficiency of sugar production at PT Madubaru during the production period of 2022. The analysis of energy efficiency in the production of granulated sugar using the Energy Productivity Ratio (EPR) method shows that in the 2022 production period which runs from May to October 2022, The EPR obtained in the months up to October 2022 shows an EPR value for electricity of 1.2 to 2.44, while for boilers it is between 1.68 and 2.45. The EPR results obtained in each period are in May 2022 with an EPR on electricity of 1.2 while the boiler is 1.16, the EPR in June 2022 is 1.72 electricity and the boiler is 1.68, the EPR in July 2022 on electricity is 1 .93 and the kettle is 1.92, the EPR in August is 1.98 electricity while the kettle EPR is 1.98, in September 2022 the electricity EPR is 2.14 while the kettle is 2.14, in October 2022 the electricity EPR is 2.44 while the kettle 2.45.The highest energy input used during the sugar production period in 2022 is sugarcane with an energy value generated of 431,885,993.55 MJ for electricity and 6,544,947,856.93 MJ for boilers. Based on EPR analysis, energy use in sugar production at PT Madubaru is still feasible.